2021
DOI: 10.1159/000515930
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against N-Methyl D-Aspartate Receptor in Psychotic Disorders: A Systematic Review

Abstract: <b><i>Objective:</i></b> The objective of this study was to provide comprehensive evidence synthesis including all available up-to-date data about the prevalence of N-methyl D-aspartate receptor (NMDAR) antibodies (ABs) in psychotic patients in order to evaluate the clinical relevance of ABs as well as to specify potential explanations of the heterogeneity of the findings and determine areas for further research. <b><i>Methods:</i></b> A literature search was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 100 publications
(288 reference statements)
0
9
0
Order By: Relevance
“…1 ) involving a mild encephalitis developing into a severe autoimmune encephalitis fulfilling the latest NMDARE criteria. A systematic review of NMDAR antibodies in psychiatric disorders pointed out that the seropositivity varies widely, ranging from 0.5 to 11.6% depending on the study population and testing methods (fixed or live cell-based assay) [ 38 ]. These authors suggested that the NMDAR autoantibodies play a role in a subgroup of psychotic patients [ 38 ].…”
Section: Nmdar Autoantibodies In Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) involving a mild encephalitis developing into a severe autoimmune encephalitis fulfilling the latest NMDARE criteria. A systematic review of NMDAR antibodies in psychiatric disorders pointed out that the seropositivity varies widely, ranging from 0.5 to 11.6% depending on the study population and testing methods (fixed or live cell-based assay) [ 38 ]. These authors suggested that the NMDAR autoantibodies play a role in a subgroup of psychotic patients [ 38 ].…”
Section: Nmdar Autoantibodies In Psychiatric Disordersmentioning
confidence: 99%
“…A systematic review of NMDAR antibodies in psychiatric disorders pointed out that the seropositivity varies widely, ranging from 0.5 to 11.6% depending on the study population and testing methods (fixed or live cell-based assay) [ 38 ]. These authors suggested that the NMDAR autoantibodies play a role in a subgroup of psychotic patients [ 38 ]. A very recent investigation highlighted a specific psychopathology that may indicate an NMDARE, such as a polymorphic psychotic symptomatology, a fluctuating course with marked cognitive dysfunction and psychotic symptoms [ 39 ].…”
Section: Nmdar Autoantibodies In Psychiatric Disordersmentioning
confidence: 99%
“…Previous studies indicated that patients diagnosed with bipolar disorder, autistic traits, or psychotic disorder presented with autoimmune encephalitis a few years after the original diagnosis (20,22,28,30), demonstrating that autoimmune encephalitis with prevalent psychiatric manifestations may be misdiagnosed and mistreated. Anti-NMDA-receptor encephalitis frequently has a relapsing course (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Psychotic manifestations are often observed among patients with autoimmune disorders ( 20 , 21 ). Anti-NMDA-receptor encephalitis might be present in a subset of patients with psychosis, and immunotherapy can be considered a treatment option for patients who fail to respond to other therapies ( 22 ). Moreover, although pure psychotic manifestations of antibody-associated autoimmune encephalitis without any additional neuropsychiatric findings are rare ( 23 ), it is easy to overlook autoimmune encephalitis, particularly when the neurological symptoms are atypical.…”
Section: Introductionmentioning
confidence: 99%
“…This refers to the study of evoked potentials, 50,51 in particular, the study of facial expressions, [52][53][54][55] the study of oculomotor alterations in patients with schizophrenia spectrum disorders 56 and autoimmune disorders in newly emerging psychotic states. [56][57][58][59] In general, the task is to carry out a network analysis of the identified disorders. [60][61][62] Thus, the research carried out at the present time preserves the tradition of an integrated clinical and social approach, on the basis of which organizational models of psychiatric services are proposed.…”
Section: Care System For Special Patient Groupsmentioning
confidence: 99%